2021
DOI: 10.1016/j.apsb.2021.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota mediates the absorption of FLZ, a new drug for Parkinson's disease treatment

Abstract: The gut microbiota plays an important role in regulating the pharmacokinetics and pharmacodynamics of many drugs. FLZ, a novel squamosamide derivative, has been shown to have neuroprotective effects on experimental Parkinson's disease (PD) models. FLZ is under phase Ⅰ clinical trial now, while the underlying mechanisms contributing to the absorption of FLZ are still not fully elucidated. Due to the main metabolite of FLZ was abundant in feces but rare in urine and bile of mice, we focused on the gut microbiota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…However, based on previous studies, MOO had poor absorption in oral administration 21 ; thus MOO's concentration in blood or brain might be very low. Many studies reported on gut microbiota interacting with drugs and affecting drug absorption 22 , 23 . A recent study showed a close relationship between the antidepressant effect of MOO and gut microbiota, although the molecular mechanism was absent 24 .…”
Section: Introductionmentioning
confidence: 99%
“…However, based on previous studies, MOO had poor absorption in oral administration 21 ; thus MOO's concentration in blood or brain might be very low. Many studies reported on gut microbiota interacting with drugs and affecting drug absorption 22 , 23 . A recent study showed a close relationship between the antidepressant effect of MOO and gut microbiota, although the molecular mechanism was absent 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Especially, the complex interaction of components in the herb pair might affect the absorption of these ingredients in many aspects, including the metabolism of gut microbiota, as well as intestine and liver metabolism [25]. Accumulating evidence demonstrated that ginsenosides could be extensively metabolized by gut microbiota, leading to competitive inhibition [26]. This competitive inhibition might reduce the degradation and increase the concentration of 6‐gingerol in the intestine, which finally enhanced the bioavailability of 6‐gingerol.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, human or animal intestine contains a rich and diverse microbiota that plays a crucial role in regulating the pharmacokinetics and pharmacodynamics of many drugs [37]. Specifically, the primary ginsenosides (e.g., ginsenoside Rb1 and Rb2) could be gradually deglycosylated by glycoside hydrolases (e.g., α‐rhamnosidase, β‐glucosidase, and xylosidase), which were present in mammalian gut microbiota, into the active secondary ginsenoside (ginsenoside CK) to improve bioavailability [26]. Indeed, substantial evidence demonstrated that the species diversity and overall community structure of the gut microflora in UC patients markedly altered [38].…”
Section: Resultsmentioning
confidence: 99%
“…The potential Parkinson's disease drug FLZ, formulated as N-2-[(4-hydroxyphenyl)-ethyl]-2-(2,5-dimethoxy-phenyl)-3-(3-methoxy-4-hydroxyphenyl)-acrylamide, was shown to be metabolized by gut microbes, and its metabolites can be rapidly absorbed into the blood where they are methylated to FLZ, and it has been shown that significant reduction in the improvement of Parkinson's disease was found with the use of antibiotics and interference of gut microbiota. 62 Oxaliplatin, an anti-tumor drug, has been shown to be influenced by gut microbes; treatment with oxaliplatin in SPF mice on antibiotics or in germ-free mice often does not have a significant therapeutic effect. This is because butyrate, a metabolite of gut microbes, promotes the efficacy of the anti-tumor drug oxaliplatin by modulating CD8 + T cells, a mechanism that is attenuated or even eliminated in mice lacking some/all gut microbes.…”
Section: Xenobiotics From Drug-microbiome Interactionsmentioning
confidence: 99%